A study on factor influencing voting behavior in Lembah Bujang / Nur Ashyikin Mohamed - Mohamed, Nur Ashyikin (2018)
The purpose of the study is to identify factors influencing voting behavior among voters. There is issue regarding swing in the interest among the voters at the constituency of Merbok (Pl 04), Kedah regarding the previous result General Election (GE) 11 th until General Election (GE) 14th• The data collected using the quantitative method by distributed questionnaire. First, this study is conducted by focusing on individual registered voters at voting district in Lembah Bujang (Dun Tanjong Dawai). The number respondents are 327 for the survey questionnaire using the formula table sample size population proposed by Sekaran and Bougie (2003). The methodologies used are descriptive statistics analysis, correlation and multiple regression using for test analysis. The result from analysis show three independent variable which influence voting behavior. Those factors are candidates' images, emotional feelings and social imagery is proposed from model the primary voters' choice behavior Newman and Sheth (1989). The result of this study shows the most dominants factors is candidates' images is influencing the voting behavior among voter in Lembah Bujang.